FORMATION OF STRATEGIC FORESIGHT MANAGEMENT COMPETENCE AMONG FUTURE FINANCE SPECIALISTS BASED ON REGIONAL ECONOMIC INTELLIGENCE IN THE ERA OF DIGITAL TRANSFORMATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
his article analyzes the theoretical and practical aspects of developing strategic foresight management competence among future finance specialists based on regional economic intelligence in the context of digital transformation. The digitalization of the modern economy, the increasing use of largescale data, and the integration of artificial intelligence technologies into financial management require professionals to possess the skills necessary for forecasting future economic processes and making strategic decisions. The study employed the analysis of scientific and pedagogical literature, comparative analysis, pedagogical modeling, and approaches based on foresight methodology. Regional economic indicators, including investment activity, employment, industrial production, and export potential, were examined as tools for developing students’ analytical, prognostic, strategic, and digital competencies. The findings revealed that
Keywords: strategic foresight management, regional economic intelligence, digital transformation, future finance specialists, prognostic competence, strategic thinking, financial education.